POLA ASUH ORANG TUA DALAM MEWUJUDKAN PENDIDIKAN AGAMA ISLAM PADA ANAK USIA PRA BALIGH DI DESA LARINGGI KECEMATAN MARIORIAWA KABUPATEN SOPPENG SULAWESI SELATAN - Trisnawaty Trisnawaty (Al-Ishlah: Jurnal Pendidikan Islam, 2023)
This study aims to determine the parenting patterns of parents in realizing Islamic religious education in pre-baligh-aged children in Laringgi Village, Marioriawa District, Soppeng Regency. This research uses a qualitative approach and a phenomenalogic method by conducting a process of finding a picture of data from the context of events directly. The results showed that parental parenting in realizing Islamic religious education in pre-baligh-aged children in Laringgi Village, Marioriawa District, Soppeng Regency, is a deliberative parenting style and parenting style for abandoning parents.